1996
DOI: 10.1093/ije/25.4.846
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Drug Users on Inpatient Hospital Care during the Human Immunodeficiency Virus Epidemic in Amsterdam

Abstract: On the total scale of inpatient hospital expenditure in Amsterdam, the contribution of illicit drug users appears to be small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In these days a relatively small proportion of the Amsterdam general hospital beds were occupied by HIV infected drugs users [14]. As a result of lifestyle concerns and strict admissions criteria, aftercare for this group was not offered by the mainstream nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…In these days a relatively small proportion of the Amsterdam general hospital beds were occupied by HIV infected drugs users [14]. As a result of lifestyle concerns and strict admissions criteria, aftercare for this group was not offered by the mainstream nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…Minimizing length of stay (LOS) for hospitalized patients infected with AIDS without reducing quality of care or increasing frequency of hospitalization is desirable. Besides being expensive (Van Haastrecht et al 1996), hospitalization days put AIDS patients at risk for nosocomial infections and disrupt their economic and social lives. To this end, many studies have found substantial (i.e., of two to four days) reductions in hospital LOS for patients infected with HIV have occurred since the mid‐1980s (Grabau, Kaufman, and Han 1991; Markson, Turner, and Fanning 1992; Paul et al 1999; Kelly, Ball, and Turner 1989; Stein 1994; Bonuck and Arno 1997).…”
mentioning
confidence: 99%